2013
DOI: 10.15837/ijccc.2013.3.244
|View full text |Cite
|
Sign up to set email alerts
|

A Rate based Congestion Control Mechanism Using Fuzzy Controller in MANETs

Abstract: The traditional congestion control mechanism TCP, performs very poorly in MANETs Because there are a number of new challenges such as wireless link error, medium contention and frequent route failures in this kind of networks [1]. In this paper, we propose a fuzzy adhoc rate-based congestion control (FARCC) to enhance the efficiency of network in MANETs. In FARCC, we use a rate-based transmission scheme using two fuzzy controller of zero order Takagi Sugeno Kang (TSK) model to congestion detection and congesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Congested networks can therefore seriously degrade network performance. Many studies [13], [20], [21], [24], [25] have shown that audio and video respond more slowly to packet loss than streaming and better match congestion mechanisms to achieve smooth throughput changes. A lot of Internet propose models have changed with the advent of new multimedia usages.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Congested networks can therefore seriously degrade network performance. Many studies [13], [20], [21], [24], [25] have shown that audio and video respond more slowly to packet loss than streaming and better match congestion mechanisms to achieve smooth throughput changes. A lot of Internet propose models have changed with the advent of new multimedia usages.…”
Section: Related Workmentioning
confidence: 99%
“…However, compared to MANET, multimedia applications face some problems due to the inherent characteristics of MANET. The rate control technique widely applied in wired networks is an "equation-based rate control" recognized as "TCP Friendly Rate Control (TFRC)" [22], [25], [27]. There are basically three benefits to rate control by means of TFRC.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations